The Incidence, Outcomes, and Risk Factors of Secondary Poor Graft Function in Haploidentical Hematopoietic Stem Cell Transplantation for Acquired Aplastic Anemia - Lin, Fan; Han, Tingting; Zhang, Yuanyuan; Cheng, Yifei; Xu, Zhengli; Mo, Xiaodong; Wang, Fengrong; Yan, Chenhua; Sun, Yuqian; Wang, Jingzhi; Tang, Feifei; Han, Wei; et al. (Frontiers in Immunology, 2022)
Secondary poor graft function (sPGF) increases the risk of life-threatening complications after transplantation after hematopoietic stem cell transplantation (HSCT). The incidence, clinical outcomes, and risk factors of sPGF have not been elucidated in haploidentical (haplo-) HSCT for acquired aplastic anemia (AA) patients. We retrospectively reviewed 423 consecutive AA patients who underwent haplo-HSCT between January 2006 and December 2020 and report a 3-year cumulative incidence of 4.62% (95% confidence interval [CI]: 3.92%-10.23%) of sPGF. While no primary PGF occurred. The median time to sPGF was 121 days (range 30-626 days) after transplantation. To clarify the risk factors for sPGF, 17 sPGF cases and 382 without PGF were further analyzed. Compared to patients without PGF, the 2-year overall survival was significantly poorer for sPGF patients (67.7% vs 90.8%, p =.002). Twelve sPGF patients were alive until the last follow-up, and 7 achieved transfusion independency. The multivariable analyses revealed that later neutrophil engraftment (OR 2.819, p=.049) and a history of refractory cytomegalovirus viremia (OR=7.038, p=.002) post-transplantation were associated with sPGF. There was weak evidence that a history of grade 3-4 acute graft-versus-host disease increased the risk of sPGF (p=.063). We advocated better post-transplantation strategies to balance the risk of immunosuppression and viral reactivation for haplo-HSCT in AA patients.